Links between identity processes and anxiety/depression in emerging adulthood - Žukauskienė, Rita; Malinauskienė, Oksana; Kaniušonytė, Goda (Psichologija, 2017)
Identity formation is a core developmental task, the importance of which is not limited to adolescence but pertains to emerging adulthood as well (Arnett, 2004). In our study, we consider a three-factor identity model (Crocetti, Rubini, & Meeus, 2008), focused on the dynamics by which emerging adults form, evaluate, and revise their identities. It is known that some identity processes are related to the internalising of problems (Luyckx et al., 2008 b; Schwartz et al., 2011) and, in turn, to the lower adjustment (Luyckx et al., 2005); thus, it is particularly important to unravel what role does the action of internalising problems – such anxiety or depression – play in the process of identity formation.The purpose of this study was to examine certain links between anxiety/depression and identity processes (identity commitment, in-depth exploration and identity reconsideration), accounting for recently matured individuals and emerging adults in Lithuania. The participants consisted of 491 emerging adults (74.7% of them were females), aged 18–29 (M = 22.5, SD = 2.97). The measures used in our study are the following: Anxiety/Depression: Adult Self-report Form (ASR) (Achenbach & Rescorla, 2003); Identity processes: The Utrecht-Management of Identity Commitments Scale (U-MICS) (Crocetti, Rubini, & Meeus, 2008). The results of SEM have shown that anxiety/depression negatively predicts commitment and in-depth exploration and positively predicts identity reconsideration (χ2 (154) = 478.9, p < 0.05, CFI/TLI = 0.94/0.93, RMSEA = 0.066 [0.059–0.072]). As for control variables, we found that age is related only with anxiety/depression, meaning that older emerging adults scored lower on anxiety/depression. Gender was related with anxiety/depression, commitment and in-depth exploration. Females in particular had scored higher on anxiety/depression and commitment, also scoring lower than males on in-depth exploration. In conclusion, the finding indicated that, when controlling for sociodemographic variables, internalised problems are related with a less adaptive identity formation.
Keywords: anxiety/depression; identity; emerging adulthood